Angles are as easy as pie. - Froman, Robert frey50 (Thomas Y. Crowell Company New York, 1975)
Discusses facts about angles and their relationship to triangles, quadrangles, polygons, and circles.
Keywords: Angle--Juvenile Literature; Angle; Geometry